2014
DOI: 10.3168/jds.2013-7655
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of dry cow antibiotics in low somatic cell count cows

Abstract: The goal of dry cow therapy (DCT) is to reduce the prevalence of intramammary infections (IMI) by eliminating existing IMI at drying off and preventing new IMI from occurring during the dry period. Due to public health concerns, however, preventive use of antibiotics has become questionable. This study evaluated selective DCT in 1,657 cows with low somatic cell count (SCC) at the last milk recording before drying off in 97 Dutch dairy herds. Low SCC was defined as <150,000 cells/mL for primiparous and <250,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 25 publications
6
126
5
5
Order By: Relevance
“…Herdlevel parameters, such as bulk milk SCC can also be taken into account. Application of a SDCT regimen, based on withholding DCT from multiparous cows with SCC <250,000 cells/mL and primiparous cows with SCC <150,000 cells/mL at the last milk recording before drying off, has been evaluated (Scherpenzeel et al, 2014). This approach significantly increased the incidence rate of CM (IRCM) and subclinical mastitis (SCM) and had potential consequences for animal welfare and economics but resulted in a substantial decrease in antimicrobial usage.…”
Section: Introductionmentioning
confidence: 98%
“…Herdlevel parameters, such as bulk milk SCC can also be taken into account. Application of a SDCT regimen, based on withholding DCT from multiparous cows with SCC <250,000 cells/mL and primiparous cows with SCC <150,000 cells/mL at the last milk recording before drying off, has been evaluated (Scherpenzeel et al, 2014). This approach significantly increased the incidence rate of CM (IRCM) and subclinical mastitis (SCM) and had potential consequences for animal welfare and economics but resulted in a substantial decrease in antimicrobial usage.…”
Section: Introductionmentioning
confidence: 98%
“…The at-risk period for a cow started at the beginning of the survey or at the date of first calving and ended at the end of the survey or at the culling date. As dry cows can suffer from CM (Scherpenzeel et al, 2014) and CM in early lactation may originate from IMI established in the nonlactating period (Bradley and Green, 2004), dry periods were included in the at-risk period. Overall IRCM (independent of the culture results), as well as pathogen-specific IRCM (Staph.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…McDougall (2010) observed that 9% of uninfected and untreated glands developed new intra-mammary infections over the dry period in pasture-grazed cows, compared to 2-2.5% protected by antibiotic DCT. Further Scherpenzeel et al (2014) reported 1.7 times higher incidence of clinical mastitis at quarter level in cows dried off without antibiotic than control. Previous studies reported lower incidence of clinical mastitis (3-6% at quarter level and 10.1-14.2% at cow level) during early lactation in dairy cows treated with DCT (Godden et al, 2003;Gundelach et al, 2011;Arruda et al, 2013;Johnson et al, 2016).…”
Section: Results and Discussion Incidence Of Clinical Mastitismentioning
confidence: 99%